Full solution processed mesostructured optical resonators integrating colloidal semiconductor quantum dots - Calvo, Mauricio Ernesto (2015)
Herein we show a solution based synthetic pathway to obtain a resonant optical cavity with embedded colloidal semiconductor quantum dots (CSQDs). The optical cavity pore network, surrounded by two dense Bragg mirrors, was designed ad hoc to selectively host the quantum dots, while uncontrolled infiltration of those in the rest of the layered structure was prevented. Coupling between the optical resonant modes of the host and the natural emission of the embedded nanoparticles gives rise to the fine tuning of the luminescence spectrum extracted from the ensemble. Our approach overcomes, without the need for an encapsulating agent and exclusively by solution processing, the difficulties that arise from the low thermal and chemical stability of the CSQDs. It opens the route to achieving precise control over their location and hence over the spectral properties of light emitted by these widely employed nanomaterials. Furthermore, as the porosity of the cavity is preserved after infiltration, the system remains responsive to environmental changes, which provides an added value to the proposed structure.